Belgicaekspedisjonen 1897-1899 : den første overvintring i Antarktis - Amundsen, Roald; Kløver, Geir O. (Red.) (Frammuseet, 2009)
Publication Title: Roald Amundsens dagbøker
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A; Myklevoll, Sigmund; Mæstad, Kjartan; Nøttestad, Leif; Alvarez, Jaime (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; krill; marin biologi; raudåte; økosystemer

A review of two decades (1986 2008) of geochronological work in Heimefrontfjella, and geotectonic interpretation of western Dronning Maud Land, East Antarctica - Jacobs, Joachim (Polarforschung, 2009)
During two decades (1986 - 2008) of geochronological work in Heimefrontfjella, nearly 130 geochronological ages were produced using a wide range of geochronological techniques. The ages fall into four broad age groups from Archaean to Cenozoic times, revealing a long and complex geological history. In general, Heimefrontfjella consists of Mesoproterozoic high grade basement related to the ∼1100 Ma Maud Belt. This basement is overlain by Permo-Carboniferous sedimentary rocks and Jurassic lavas. Archaean and Palaeoproterozoic detrital zircon ages are recorded from meta-sedimentary rocks probably characterizing the foreland of the Maud Belt. The protolith and metamorphic ages of the Mesoproterozoic Maud Belt fall into two groups. An older age group from ∼1200-1100 Ma is related to back-arc and island arc volcanism. High-grade metamorphism in the Maud Belt is dated between 1090-1060 Ma and is thought to reflect continent-continent collision, possibly related to the formation of Rodinia. Regional cooling to below 500-300 °C at ∼1010-960 Ma in part of the mountain range might indicate rifting of Rodinia. The eastern part of the mountain range is overprinted by the ∼600-500 Ma East African-Antarctic Orogen. The orogenic front of this major mobile belt is exposed in the study area as the Heimefront Shear Zone. East of this major lineament all Ar-Ar, K-Ar and Rb-Sr mineral ages are reset to ∼500 Ma. Initial Gondwana rifting affected the area at c. 180 Ma, when the Bouvet/Karroo mantle plume caused dynamic uplift of the area, followed by burial underneath up to 2 km of Jurassic lava. This led to tempering of the basement up to about 100 °C, as indicated by apatite fission track data. The lava pile underwent erosion in Cretaceous time, when renewed rifting affected the region. Latest tectonic movements might be related to Cenozoic ice loading related to the built up of the Antarctic ice sheet.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung und Deutsche Gesellschaft für Polarforschung Place: Bremerhaven, Germany ISBN: 2190-1090
Keywords: Dronning Maud Land; ekspedisjoner; geokronologi; geologi; tektonikk

Cold recall: reflections of a polar explorer - Kløver, Geir O (Fram Museum, 2009)
Keywords: Antarktis; ekspedisjoner; historie

Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung und Deutsche Gesellschaft für Polarforschung Place: Bremerhaven, Germany ISBN: 2190-1090
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging